2013
DOI: 10.3945/an.112.003533
|View full text |Cite
|
Sign up to set email alerts
|

Potassium and Health

Abstract: Potassium was identified as a shortfall nutrient by the Dietary Guidelines for Americans 2010 Advisory Committee. The committee concluded that there was a moderate body of evidence of the association between potassium intake and blood pressure reduction in adults, which in turn influences the risk of stroke and coronary heart disease. Evidence is also accumulating of the protective effect of adequate dietary potassium on age-related bone loss and reduction of kidney stones. These benefits depend on organic ani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
156
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(189 citation statements)
references
References 90 publications
(90 reference statements)
5
156
0
6
Order By: Relevance
“…16 Magnesium is an important "helper molecule" of many enzymes mainly involved in energy metabolism, production of protein and for maintaining electrical potential of nerve tissue and cell membranes. 17 There is an important role of sulphur in synthesis of protein, regeneration of cells and cleansing of blood. 18 The presence of these important elements in Cleome viscosa…”
Section: Elemental Analysismentioning
confidence: 99%
“…16 Magnesium is an important "helper molecule" of many enzymes mainly involved in energy metabolism, production of protein and for maintaining electrical potential of nerve tissue and cell membranes. 17 There is an important role of sulphur in synthesis of protein, regeneration of cells and cleansing of blood. 18 The presence of these important elements in Cleome viscosa…”
Section: Elemental Analysismentioning
confidence: 99%
“…This finding is somewhat intriguing if salty snacks are taken in consideration although the link between high salt intake and hypertension is still a matter of scientific debate [21]. A plausible explanation of the inverse association found in our study could be related to the beneficial effect of healthy snacks, such as fruits, known for their high potassium content [22].…”
Section: Discussionmentioning
confidence: 66%
“…It has been suggested that individuals with diets that are low in potassium are particularly vulnerable to the hypertensive effects of high sodium intake [20,21]. Hence, the ratio of sodium-to-potassium may be more reliable than either nutrient alone in predicting the risk of cardiovascular disease [22,23]. In addition to sodium, potassium can also be determined accurately in 24h urine collections, hence avoiding the need to rely on reported dietary intake data and national up-to-date food composition tables.…”
Section: Introductionmentioning
confidence: 99%